Performing Religious Services in Trading Interaction - Ali Halidin; Sitti Zakiah; Mahsyar Mahsyar (Alfaz (Arabic Literatures for Academic Zealots), 2019)
There are two communication approaches had been mentioned in this study, firstly: the cultural communication strategy, and the second: communication habit. Cultural communication seeks to describe the interests that was built by seeing the opportunities and the benefits of the trade that was occurred between the merchant community around on the two holy lands of Medina and Mecca to the visitors and pilgrims or commonly referred to as umrah pilgrims. There are two trading strategies with the use of the Indonesian language. The firstly because of the largest number of Umrah pilgrims each year to the Nabawi Mosque in Medina and illegitimate mosques in Makkah (alharam). Secondly, the habitual communication, namely mapping cultural ties was not only done by the marriage or kinship relations assimilation), but this is the cultural linkage can occur because each individual has the same interests or needs each other. The method used was descriptive qualitative, by observing, the real communication patterns was happened between Indonesian Umrah pilgrims and traders from Arab and Middle Eastern communities around the Nabawai mosque of Medina and the Haram Makkah. The specific communication pattern is trading communication with the approaching to the cultural elements and Indonesian nationalism in it, so that the impression is more interesting. It’s looked the merchants around the two holy lands were good at attracting the interest and enthusiasm to the shopping for the visitors and pilgrims from Indonesia, by greeting and offering prices using Indonesian language. While the Indonesian pilgrims are well known having the strong nationalism and cultural culture, so the flavors arose, such as feel in the village themselves and having kinship if they heard the mother's language and culture used by others.